The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1381/096089298765555015
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Banded Gastroplasty at More than 5 Years

Abstract: VBG is, in our experience, a safe and technically simple operation, but the long-term results are questionable. The reoperation rate was high, and weight loss and quality of life are superior with other operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 11 publications
1
27
0
5
Order By: Relevance
“…This study indicates that long term nutritional monitoring, and clear and appropriate dietetic advice on diet quality, together with adherence to an appropriate multivitaminamineral supplement, is essential. Our conclusion can at present only be applied to one year post surgery, as longer term review has not yet been completed, but our data and that from other studies, 14,20 suggests that there may be ongoing issues of concern, requiring nutritional intervention and support. This is in line with the National Institutes of Health (NIH) Consensus Development Conferences report, 21 emphasising the importance of a multidisciplinary approach involving surgeons and nutritionists, in the care of severely obese patients.…”
Section: Resultsmentioning
confidence: 72%
“…This study indicates that long term nutritional monitoring, and clear and appropriate dietetic advice on diet quality, together with adherence to an appropriate multivitaminamineral supplement, is essential. Our conclusion can at present only be applied to one year post surgery, as longer term review has not yet been completed, but our data and that from other studies, 14,20 suggests that there may be ongoing issues of concern, requiring nutritional intervention and support. This is in line with the National Institutes of Health (NIH) Consensus Development Conferences report, 21 emphasising the importance of a multidisciplinary approach involving surgeons and nutritionists, in the care of severely obese patients.…”
Section: Resultsmentioning
confidence: 72%
“…Within the EC IIb studies, 72 70 to 86% 79 were very satisfied with the operation; within the EC III studies, the rate even went up to 90%. 95 A minority of patients disapproved the result of the operation, ranging from 4.2 70 to 18% 79 within the EC IIb and EC III studies, respectively.…”
Section: General Quality Of Lifementioning
confidence: 96%
“…Satisfaction with obesity surgery A total of 11 studies, five corresponding to EC IIb 62,66,70,79,88 and six to EC III, 35,75,81,83,89,95 asked patients about their satisfaction with the operation. Within the EC IIb studies, 72 70 to 86% 79 were very satisfied with the operation; within the EC III studies, the rate even went up to 90%.…”
Section: General Quality Of Lifementioning
confidence: 99%
“…No entanto, cerca de 10% dos pacientes não consideraram que as suas expectativas pré-cirúrgicas se tivessem realizado. Isto vai de encontro à conclusão de uma revisão sistemática [29] da literatura conduzida por Herpertz et al , onde se verificou que a insatisfação com os resultados pós-39 [40] cirúrgicos variava entre 4.2% e 18% . É importante realçar também que além dos 15% de pacientes insatisfeitos com a rapidez de perda de peso, todos os participantes referiram que se sujeitariam de novo à cirurgia bariátrica.…”
Section: Resultsunclassified
“…This reflects the conclusion from a systematic literature review conducted by Herpertz et [29] al. where they found that dissatisfaction with post- [40] surgical results varied between 4.2% and 18% . It is also important to note that besides the 15% of patients who were unsatisfied with the pace of weight loss, all participants reported that they would undergo bariatric surgery again.…”
Section: Discussionmentioning
confidence: 99%